Water-Soluble Polymer Assists N-Methyl-D-Aspartic Acid Receptor 2B siRNA Delivery to Relieve Chronic Inflammatory Pain In Vitro and In Vivo - Jie Peng; Jiahui Ma; Xue Yang; Huan He; Haopeng Wu; Tongtong Ma; Jianhua Lu (Pain Research and Management)
We constructed a water-soluble lipopolymer (WSLP) as a nonviral gene carrier to deliver siRNA targeting NR2B. The cytotoxicity and serum stability of WSLP loaded with siRNA were evaluated, and the knockdown efficiency of WSLP/NR2B-siRNA in PC12 cells was examined. The results showed that WSLP could protect the loading siRNAs from enzymatic degradation in serum and exhibit low cytotoxicity to cells. After transfection, WSLP/NR2B-siRNA complexes reduced the NR2B transcriptional level by 50% and protein level by 55% compared to control siRNA. Moreover, 3 days after intrathecal injection of WSLP/NR2B-siRNA complexes into rats, the NR2B protein expression decreased significantly to 58%, compared to control treatment (p<0.01). Injection of WSLP with scrambled siRNA or of polyethylenimine (PEI) with NR2B-siRNA did not show this inhibitory effect. Additionally, injection of WSLP/NR2B-siRNA complexes significantly relieved inflammatory pain in rats at 3, 4, and 5 days with reduced MWT and decreased TWL scores, while injection of WSLP with scrambled siRNA or of PEI with NR2B-siRNA did not. These results demonstrated that WSLP can efficiently deliver siRNA targeting NR2B to PC12 cells and relieve pain in rats with chronic inflammatory pain.